2013
DOI: 10.1002/jps.23550
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nitrate Metabolism and Action: Toward a Unifying Hypothesis and the Future—A Dedication to Professor Leslie Z. Benet

Abstract: This review summarizes the major advances that had been reported since the outstanding contributions that Professor Benet and his group had made in the 1980’s and 1990’s concerning the metabolism and pharmacologic action of organic nitrates (ORN). Several pivotal studies have now enhanced our understanding of the metabolism and the bioactivation of ORN, resulting in the identification of a host of cysteine-containing enzymes that can carry out this function. Three isoforms of aldehyde dehydrogenase, all of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 135 publications
0
9
0
1
Order By: Relevance
“…Biotransformation of organic nitrates is not fully understood and can vary widely with the class of organic nitrate 59. Organic nitrates typically undergo liver first‐pass metabolism; however, the exact mechanism of denitration (release of NO) in the vasculature or different tissue sites remains a matter of debate 60, 61. Organic nitrates have potent acute effects, while the metabolic conversion of inorganic nitrate to nitric oxide is more efficient under hypoxic and acidic conditions that may not have been reproduced under these study conditions 57.…”
Section: Discussionmentioning
confidence: 99%
“…Biotransformation of organic nitrates is not fully understood and can vary widely with the class of organic nitrate 59. Organic nitrates typically undergo liver first‐pass metabolism; however, the exact mechanism of denitration (release of NO) in the vasculature or different tissue sites remains a matter of debate 60, 61. Organic nitrates have potent acute effects, while the metabolic conversion of inorganic nitrate to nitric oxide is more efficient under hypoxic and acidic conditions that may not have been reproduced under these study conditions 57.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the cumulative amounts of 1, 2-GDN to 1, 3-GDN formed, measured at 120 minutes, after the reaction between 100 nM of NTG and rALDH3A1, was 5.21 (Fig. 3A) compared to the observed ratios of 9.0 and 4.98 for rALDH1A1 [7] and ALDH2 purified from mouse macrophage cells [1], respectively, at the same added NTG concentration. Thus, 1, 2-GDN is the primary metabolite of NTG metabolism by all three isoforms of ALDH.…”
Section: Discussionmentioning
confidence: 92%
“…However, it was shown that the relaxation potencies of NTG and IS-5-MN were identical in ALDH1A1 wildtype and knockout mice [7], suggesting that this isoform may not be relevant to mediate ORN bioactivation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In order for nicorandil to work in a cell, we concluded that it would be necessary to prevent or at least slow down denitration through metabolic processes. The primary enzyme responsible for metabolizing nitroglycerin and releasing nitric oxide is ALDH2 [34, 35]; this enzyme has also been shown to release nitric oxide from other organic nitrates, including nicorandil [36, 37]. ALDH2 can be inhibited by the drug daidzin [38, 39]; thus, we pre-treated sensory neurons with nicorandil alone (100 μM for 1 hour prior to and throughout cisplatin), daidzin alone (10 μM 3 days prior to and throughout cisplatin), and nicorandil plus daidzin and compared DNA damage following treatment with cisplatin as assessed by levels of phosphorylated γ-H2AX.…”
Section: Resultsmentioning
confidence: 99%